PENGARUH BAURAN PEMASARAN TERHADAP MINAT MASYARAKAT DALAM MEMILIH RUMAH KOS DI SAMARINDA - Sriwahyuni Paembong; Adisty Shabrina Nurqamarani; Eddy Soegiarto (LPPM University 17 Agustus 1945 Samarinda, 2019)
This study aims to determine the effect of product, price, promotion, location, people, physical evidence and process on people’s Interest in Choosing Boarding Houses in Samarinda. Data were obtained from the results of the distribution of questionnaires. The population of this study is people in the city of Samarinda who are looking for boarding houses with a sample of 30 people. The analytical tool used is multiple linear regression in which the classical assumption has been done first. Based on the results of the study and discussion, there is a positive and significant influence between the product on people's interest in choosing a boarding house in samarinda. There is a positive but insignificant influence between the influence of price, promotion, location, people, physical evidence and process of the public interest in choosing a boarding house in Samarinda. From the results of this study, it is expected that boarding house owners can adjust the price of boarding houses with better facilities, do not provide prices that are not comparable to the facilities obtained by boarders who rent and can repair damaged boarding house facilities, so that the community or students have an interest in renting the boarding hous. For the next researcher, it is recommended to add more samples and other variables